تقييم مخاطر الكوارث الـزلـزالـيـة بواسطة نظم المعلومات الجغرافية دراسـة حـالـة (مـنـطـقـة كـفـر سـوسـة - دمـشـق) - جمال عمران; هالة حسن; حسين صالح; كندة ملكي (Tishreen University, 2019)
The literatures of disaster management in the 21st century denote to the lack of informatics supplies, research ways, and developed techniques which can be used in perfect treatment for disaster risk management and limit its impact on local region. This study states the importance of adapting the developed techniques that based on the methods and computational programs that take in to the account the scientific research and the technical development in insuring the practical processing of disaster risk. These techniques help the decision makers to understand the relationship between the causes and results thoroughly, also measure and analysis the performance gap between the perfect model and the local performance according to disaster. These techniques support the analytical scientific and practical study which related to disaster before and through its incidence to understand its effects, dimensions, and the way of dealing with its huge effects well. Using these new techniques and scientific approach is one of analytical tool to evaluate and present alternative solutions which increase the performance and decrease the cost after disaster. The huge collected data is in progress to treat the disasters, and that is necessary to find out the developed ways of research and the mechanism of modeling the data effectively, properly, economically, and at the same time quickly. تشير دراسات إدارة الكوارث في القرن الواحد والعشرون إلى قلة المخزون المعرفي والطرق البحثية والتقنيات المتطورة التي يمكن استخدامها في المعالجة المثالية لإدارة خطر الكوارث والحد من تأثيراتها على المستوى المحلي. يبين هذا البحث ضرورة تبني التقنيات المتطورة المبنية على الطرق والبرامج الحاسوبية التي تأخذ في الحسبان البحث العلمي والتطوير التقاني في تأمين المعالجة العملية لخطر الكوارث. تساعد هذه التقنيات أصحاب القرار على الفهم الدقيق للعلاقات بين الأسباب والنتائج، وقياس وتحليل الفجوة في الأداء بين النموذج المثالي والأداء المحلي لمعالجة تأثيرات الكارثة. تؤمن هذه التقنيات الدارسة التحليلية العلمية والعملية لهذه الكوارث قبل وخلال وقوعها لكي يتم فهم تأثيرها وأبعادها وكيفية التجاوب بشكل أفضل مع آثارها الجسيمة. إن استخدام التقنيات الحديثة والمنهج العلمي يعتبر احد الأساليب التحليلية لتقييم وطرح الحلول البديلة والكفيلة برفع الأداء وتقليل التكلفة الناجمة عن الكوارث. يتزايد الكم الهائل من البيانات المجمعة لمعالجة هذه الكوارث باطراد وهذا ما يستلزم البحث عن طرق البحث المتقدمة والآلية لنمذجة هذه البيانات بأسلوب فعال ومتناسب واقتصادي وسريع بالوقت ذاته.